Author Correction: Pharmacological rescue in patient iPSC and mouse models with a rare DISC1 mutation - Nam-Shik Kim; Zhexing Wen; Jing Liu; Ying Zhou; Ziyuan Guo; Chongchong Xu; Yu-Ting Lin; Ki-Jun Yoon; Junhyun Park; Michelle Cho; Minji Kim; Xinyuan Wang; et al. (Nature Communications, 2021)
https://doi.org/10.1038/s41467-021-23263-0